KAJIAN YURIDIS PELAKSANAAN PENERBITAN SERTIPIKAT PENGGANTI TERHADAP SERTIFIKAT HAK ATAS TANAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi di Kantor Pertanahan Kabupaten Magetan) - SAWINING, GRISNA (Dinamika Hukum, 2020)
The purpose of thisresearch is to assess and analyse the implementation of a replacement of the surrogate against the land rights certificate in Magetan District office. To study and analyze the barriers experienced by the land office of Magetan Regency in the implementation of a replacement sertificate against the certificate of land rights. The method of approach in writing is sociological juridical. The specification of this research uses analytical descriptive. Data sources use primary data and skunder data. Data collection techniques using interview studies, Focus Group Discussion and the library. To analyze the data, researchers use qualitative descriptive analysis methods. Implementation of a sertificate issuance of the right to land because it was lost by the land Office Magetan District has been in accordance with PP number 24 year 1997 about land registration and regulation of the Minister of Agrarian state/head of national Land No. 3 year 1997 about the implementation of government Regulation number 24 year 1997 about land registration, that is done with the following procedure: To create a cover letter in the village, report the loss of land sertificate to the police station, To block the land's serotyping, reported loss of landslides to the Magetan district office, oath taking, announcements in print, remeasurement of land and replacement of the substitute sertificate. The constraints faced in the implementation of a sertificate issuance of the right to land because lost by the land Office of Magetan District are as follows: documents belonging to the applicant are incomplete, the schedule of an unclear vows, the costs that should be incurred in the implementation of the issuance of the replacement of the rights to the land because the lost is considered too large by the applicant and the information provided by the Land Office of Magetan District was not received properly by Applicant. Keywords: Publication of the surrogate and the land rights certificate.